Influence of Ramadan dialectics (physical & spiritual) during Psychological preparation of young football players - Djamal, ABBAS (Sciences humaines; Vol. 37 (2014): SCIENCES HUMAINES(Novembre), 2014)
إن عملية التحضير النفسي الرياضي لا يمكن تجاهلها أبدا، فالعديد من الاختبارات النفسية تم وضعها لأجل التمكّن من تحسين مؤشرات الأداء الجيّد وتحقيق الغايات النبيلة، كون العامل الأفضل للحالة الجيّدة نفسيا والرضا في الحياة ينشأ عن المشاركة في الممارسة الرياضية بصورة منتظمة، كما تعدّ الأساس المادي الملموس الذي يتوقف عليه البناء النفسي الاجتماعي والروحي للفرد، علما بأن الطريق المؤدي إلى النجاح الفردي حسب القاعدة المتداولة يضّم ثلاثة عوامل بيولوجية، نفسية وإجتماعية، فعلم مورفولوجيا الرياضة يسمح بتشخيص التدريب إعتمادا على خصائص أنماط الجسم  Somatotypeقصد الانتقاء والتوجيه وبما أن الجسد وسيلة لتبليغ مقاصد الروح، في الثنائية الجدلية القائمة بين البدن والروح خاصة في الوسط الرياضي الاحترافي، كان الدافع إلى إبراز تأثير شهر رمضان وأيام الصيام في الوسط الرياضي قبل، أثناء وبعد المنافسة الرياضية وعلاقته بالضغوطات، الاضطرابات النفسية الناتجة عن التغيرات الايضية الفسيولوجية التي تحدث خلال ساعات الصيام ومتطلبات رهانات المنافسة التي تعدّ كأوامر قطعية للفوز.* During the holy month of Ramadan, the period of food and liquid intake depends on sunset and sunrise. Ramadan moves back in the calendar by about ten days a year. Thus, the probability that major sporting events being held during Ramadan is great, developing practical and appropriate strategies to ensure competitiveness to athletes and players regarding health, psychological aspect and physical performance becomes a significant issue; the psychological aspect appearing through the motivation may constitute a very important measure helping to face stress and anxiety, induced by the sudden change of the way of life in Ramadan. Generally, during the second week, we may observe, on one hand, a progressive human adaptation of the young athletes and, on the other hand, a disturbance in the biological rhythm which leads to a level of tolerance to the temporary pain, thus to behavioural problems. In the present approach, we will deal with dialectics between physical and spiritual aspects of Ramadan related to the corporal and psychological preparation of young Algerian football players of ten 10clubs in the first professional league, so that to preserve performance and general health, the important psychological preparation of some personality tests which currently exists for the development the indices of the performances and to achieve the goals noble since the favourable factor of better psychological state in the life, * Key Word: Psychological preparation, Ramadan, physiological preparation, individual spiritual, elite sports